1993
DOI: 10.1073/pnas.90.9.4022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rat neutral and basic amino acid transporter utilizing anti-peptide antibodies.

Abstract: High-titer, site-specific antibodies have been produced against the rat kidney broad-spectrum, sodiumindependent neutral and basic amino acid transporter (NBAATr) whose cDNA we cloned earlier. These antibodies have allowed us to characterize the transporter protein in normal rat tissues and in various cellular and in vitro expression systems. Western analysis detected 84-to 87-kDa glycosylated species enriched in rat renal and jejunal epithelial cell brush border membranes. In vitro translation of NBAA-Tr comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Six synthetic peptides representing sequences within rat NBAT were used as antigens for the production of rabbit antisera directed against NBAT. Details of peptide synthesis, production of the antisera, and evaluation of their specificity have been described previously [9,14]. The immunoglobulin (IgG) fraction from each antiserum was purified using a rProtein A antibody purification kit from Repligen (Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six synthetic peptides representing sequences within rat NBAT were used as antigens for the production of rabbit antisera directed against NBAT. Details of peptide synthesis, production of the antisera, and evaluation of their specificity have been described previously [9,14]. The immunoglobulin (IgG) fraction from each antiserum was purified using a rProtein A antibody purification kit from Repligen (Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were subjected to SDS-PAGE under both reducing and non-reducing conditions. Under reducing conditions, only the 87 and 89 kDa bands representing the glycosylated NBAT monomers produced in oocytes [14] are seen (Fig. 3, lane 1).…”
Section: Relationship Of the Heterodimer To Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…No functional rBAT Is Responsible for L-Cystine Uptake in OK Cellsexpression of the amino acid transport activity associated with rBAT has been obtained in mammalian cells (e.g. COS cells) (30). All the data previously reported on the amino acid transport activity associated with rBAT were obtained in Xenopus oocytes (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 91%
“…Indirect evidence suggested that rBAT forms a heterodimeric structure of 125 kDa with an unidentified protein of 40 -50 kDa in renal brush border membranes and oocytes (29). 2 In addition, transient expression of rBAT in COS cells revealed either expression of rBAT in the cell surface without concomitant amino acid transport activity (30) or a protein product that does not reach the plasma membrane. 3 Thus, no cell system other than oocytes has shown expression of amino acid transport activity associated with rBAT.…”
Section: The Nucleotide Sequence(s) Reported In This Paper Has Been Smentioning
confidence: 99%